Capillary rise in superhydrophilic rough channels - Kim, Jungchul; Moon, Myoung-Woon; Kim, Ho-Young (AMER INST PHYSICS, 2020)
Surface tension forces enable a liquid to rise against gravity when wettable tubes or porous media are in contact with the pool of liquid. While the rise dynamics in the media of homogeneous porosity are well known, those in heterogeneous porous media still remain poorly understood. Here, we employ a vertical channel formed by two parallel plates decorated with micropillars, as a simple model of bidisperse porous media, and observe the rise dynamics of various viscous liquids. We find the bulk rise speed to be higher than that in dry smooth channels but equal to that between prewetted smooth channels. As the bulk approaches its equilibrium height, a film emerges ahead of the bulk meniscus, which is driven by the high surface energy of the microdecorated surface. The film extension grows initially like t but later like t(1/2), with t being time. We construct theoretical models to predict the critical height where the film emerges and to rationalize the power laws of the film extension. In particular, we show that the dominant viscous resistance to the film extension is provided by the flow from the reservoir through the bulk in the early stages and by the film itself in the late stages. Our study opens a pathway to scrutinize the complicated flow dynamics arising within and across voids of heterogeneous porous media with an easily observable experimental setup of a well-defined geometry. Published under license by AIP Publishing.
Keywords: INTERFACE; DYNAMICS; FLOW